The European City – a Model for Future Urban Development and its Elements - Adam, Brigitte; Fritzsche, Stefan (DIE ERDE – Journal of the Geographical Society of Berlin, 2012)
Cities in Europe have slowly evolved and developed over several centuries. During quite a long period we have seen phases of rise and of decline of cities in Europe. Before the period of industrialisation, feudalism, trading and the growing importance of national states influenced and shaped cities as well as city networks in Europe. Industrialisation, a phenomenon of the modern age, again produced new cities and also an enormous growth of European cities. Urban development policy in Germany has set the focus on the “European city”. The article concentrates on how the term is used in German urban development policy and on the challenges German cities are confronted with. Expectations addressed to the European city model are reflected. Imports as well as exports of this type of city are considered. The findings lead to conclusions on the importance of the European city as a model and guiding vision in urban planning.